Wonder Woman. Love and murder - Picoult, Jodi 1966-; Johnson, Drew.; Marston, William Moulton 1893-1947. (New York DC Comics, 2007)
Wonder Woman, in her disguise as Diana Prince, a special agent of the Department of Metahuman Affairs, takes on an assignment to track down Wonder Woman, an impossible task that risks revealing her secret identity.
"Wonder Woman created by William Moulton Marston."
"Originally published in single magazine form in Wonder Woman #6-10"--T.p. verso.
UCWS-3009g donated by Michelle G. Ong - June 2017
Keywords: Wonder Woman -- (Fictitious character) -- Comic books, strips, etc; Science fiction comic books, strips, etc. -- Japan -- Translations into English; Graphic novels